Cell-autonomous PLCβ1 modulation of neural stem/progenitor cell proliferation during adult hippocampal neurogenesis - Song, Bo kyung; Kim, Chong-Hyun (Elsevier BV, 2022)
PLCβ1 null mouse, a model for epilepsy/schizophrenia, shows enhanced moving activity, seizures, and excessive neurogenesis in the DG of the hippocampus. Since physical or epileptic activity increases neurogenesis, we asked whether the increase of neurogenesis in PLCβ1 null mice was mainly due to the loss of PLCβ1 in stem cells or from in vivo effects of the enhanced movement or seizures of null mice. To avoid in vivo effects, we did neurosphere cultures from the DG of the adult hippocampus and quantified the cell proliferation. We found an increase in the number and size of neurospheres in KO mice cultures, which was similar to the enhancement of in vivo proliferation of DG newborn cells in KO mice. Moreover, the positive effect of high KCl treatment on the proliferation of neurosphere culture was occluded in KO mice. Further DG neurons of PLCβ1 KO mice display increased excitability, consistent with a model for epilepsy. In conclusion, these results suggest cell-autonomous inhibitory roles of PLCβ1 in the proliferation of adult neural stem/progenitor cells in vivo and the excitability of DG granule cells.